Pendekatan linguistik kognitif dalam pemerian "di antara" / "antara" (Jurnal Bahasa, 2005)
This paper examines the prescriptions on the usage of "di antara" and "antara" in the Tatabahasa Dewan (1993). Among others, the prescription includes that (a) only `di antara' can be used to indicate physical locations or directions [by implication this means that "antara"without the preposition "di" cannot be used to indicate physical location or di-rection] ; (b) "antara" is used to indicate comparisons; (c) "antara" when anteceded by a common noun, the noun cannot be duplicated; (d) "antara" can be anteceded by a cardinal number and a measure word but cannot be followed by an ordinal number; (e) "antara" can be followed by a pronoun; and "di antara" and"antara" can be matched with the prepo-sition "dengan" but not with the conjunction "dan". The corpus study undertaken reveals that users preferred the usage that are regarded as errors by prescriptive rules. Taking the position of practical grammar, the paper suggests a usage of "antara" and "di antara" based on cogni-tive linguistics. An alternative description which can account for the differences in the usage of the two structures in terms of differences in conceptualization. It is argued that the selection between "antara" and "di antara" is based on the cognitive abilities and can be related to more universal cognition and experiences of the speakers